Protective Role of PEDF-Derived Synthetic Peptide Against Experimental Diabetic Nephropathy - Ishibashi, Y.; Matsui, T.; Taira, J.; Higashimoto, Y.; Yamagishi, S. (Hormone and Metabolic Research, 2016)
Pigment epithelium-derived factor (PEDF) is a glycoprotein with complex neuroprotective, anti-angiogenic, and anti-inflammatory properties, all of which could potentially be exploited as a therapeutic option for vascular complications in diabetes. We have previously shown that PEDF-derived synthetic peptide, P5-3 (FIFVLRD) has a comparable ability with full PEDF protein to inhibit rat corneal neovascularization induced by chemical cauterization. However, the effects of PEDF peptide on experimental diabetic nephropathy remain unknown. To address the issue, we modified P5-3 to stabilize and administered the modified peptide (d-Lys-d-Lys-d-Lys-Gln-d-Pro-P5-3-Cys-amide, 0.2 nmol/day) or vehicle to streptozotocin-induced diabetic rats (STZ-rats) intraperitoneally by an osmotic mini pump for 2 weeks. We further examined the effects of modified peptide on human proximal tubular cells. Renal PEDF expression was decreased in STZ-rats. Although the peptide administration did not affect blood glucose or blood pressure, it decreased urinary excretion levels of 8-hydroxy-2′-deoxyguanosine, an oxidative stress marker, and reduced plasminogen activator inhibitor-1 (PAI-1) gene expression, and suppressed glomerular expansion in the diabetic kidneys. High glucose or advanced glycation end products stimulated oxidative stress generation and PAI-1 gene expression in tubular cells, all of which were significantly suppressed by 10 nM modified P5-3 peptide. Our present study suggests that PEDF-derived synthetic modified peptide could protect against experimental diabetic nephropathy and inhibit tubular cell damage under diabetes-like conditions through its anti-oxidative properties. Supplementation of modified P5-3 peptide may be a novel therapeutic strategy for diabetic nephropathy.
Keywords: AGEs; oxidative stress; PEDF; diabetic nephropathy; RAGE